Persepsi Pemilih Pemula mengenai Penerapan Sistem E-Voting pada Pemilu 2024 - Arianti, Gusmia (Universitas Al Azhar Indonesia, 2023)
National development is currently leading to the implementation of digital transformation, including digitalization in the electoral sector. The discourse on the implementation of an e-voting system in the Pemilu 2024 As people who are voting for the first time in general elections, beginner votes are expected to participate in the success of democratic contestation in Indonesia by understanding the implementation of the e-voting system in the 2024 elections launched by the government. This study aims to identify the perceptions of beginner votes regarding the implementation of the e-voting system in the Pemilu 2024. The research was conducted with a quantitative descriptive approach through a survey of 90 students of the Faculty of Social and Political Sciences, University of Al Azhar Indonesia, aged 17-21 years. The perceptions of beginner votes regarding the implementation of the e-voting system in the Pemilu 2024 are seen from three perception indicators, namely perceived usefulness of the system, perceived ease of use, and perceived risk. The perceived ease of use is important because by using e-voting, voting and recapitulation of vote count results can be done more quickly, accurately, transparently, and accountably. The e-voting system is considered more effective and efficient because it can save election costs, and can be done anywhere. The risk of implementing this system is considered lower than in conventional elections, especially in determining DPT and recapitulating vote count results. Novice voters agree with the implementation of the e-voting system in the 2024 elections by considering aspects of infrastructure and human resources.